Primary splenic torsion in dog as a cause of atypical acute abdomen - Marinho, Paulo Vinícius Tertuliano; Minto, Bruno Watanabe [UNESP]; Avante, Michelle Lopes [UNESP]; Cardoso, Lorena Damasio; de Vasconcellos Aquino, Gabriel; Feitosa, Caroline Cezaretti; De Nardi, Andrigo Barboza [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: A primary splenic torsion occurs when the organ rotates around its vascular pedicle in the absence of any other concomitant disease. The occurrence of primary splenic torsion is rare, with a prevalence lower than 1%. Splenic torsion is more often related to dilated gastric volvulus syndrome, and it has no clear etiology despite reports that associate it with congenital abnormalities or traumatic ruptures of the gastrosplenic or splenocolic ligaments. This study reports a case of splenic torsion in an American Pit Bull terrier dog, its related symptomatology, and the treatment adopted. Case: A 3-year-old male American Pit Bull terrier dog weighing 32 kg was admitted to the hospital with symptoms of acute abdomen, lethargy, increased abdominal volume, discomfort, restlessness, and with a history of collapse three days prior to admission. Clinical examination revealed lethargy, pale mucous membranes, reduced capillary refill time, moderate dehydration, and hyperthermia. Abdominal palpation revealed increased abdominal volume in the epigastric and mesogastric areas. CBC and serum biochemistry profile revealed hypochromic normocytic anemia, leukocytosis with absolute neutrophilia and eosinopenia, mild hypoalbuminemia, and thrombocytopenia. PCR for detection of Babesia sp. and Ehrlichia sp., which returned negative results, and measurement of clotting time, which was prolonged, were performed to exclude immune-mediated hemolytic anemia. Radiographic and ultrasonographic images showed a normal stomach, but revealed presence of splenomegaly. An exploratory laparotomy allowed direct observation of the spleen, which exhibited an increased volume, a blackened, cold, hyperemic appearance, and a complete torsion of the splenic vascular pedicle; the surgical team opted to perform total splenectomy rather than undoing the pedicle twist. The animal returned to the hospital after 10 days exhibiting an excellent clinical condition. Healing of the incisional wound was satisfactory, with formation of epithelial tissue throughout its extension. Thirty days after the surgery, the hematological parameters were within normal ranges. The animal was discharged, and its owner received information on adequate nutrition. Discussion: Clinical evaluation of symptoms of discomfort and increase in abdominal volume, especially on the left side, together with the information of the anamnesis, led to a suspicion of splenic torsion in this case. Splenic torsion can exhibit numerous clinical signs; here, ultrasound imaging allowed diagnosis of this condition. The anemia observed by means of the hematological tests could be explained by sequestration of red blood cells by the rotated spleen, with and inflammatory leukogram resulting from inflammation of the poorly perfused parenchyma, local peritonitis, and, possibly, increased release of neutrophils from the bone marrow. Thrombocytopenia and prolonged clotting time may be secondary to splenic torsion, as shown in this case. Splenectomy is the treatment of choice in cases of acute splenic torsion. This procedure is relatively easy to perform. Additionally, merely undoing the torsion does not prevent its recurrence, and may allow necrotic debris to reach the circulation. No intercurrences or involvement of adjacent organs were observed in this patient. This is due to factors such as early diagnosis, preoperative stabilization of the patient, and the short time between diagnosis and the surgical procedure, reiterating its importance in emergency conditions such as splenic torsion.
Torção esplênica primária em cão como causa atípica de abdômen agudo
Keywords: Dogs; Emergency therapy; Radiography; System lymph; Ultrasonography